Democracy through Election - Muhammad Siddiq Armia (Jember University Press, 2018)
After amendment the 1945 Constitution, Indonesia has adopted election mechanism to implement a value of democracy. Unfortunately, the regulations as a main tool have not completely covered all of election issues. It follows that the election legal systems have only been prepared for the post-election dispute instead of the pre-election dispute. This case happened in the province of Aceh. On one hand Aceh has its own law regarding the autonomy province, on the other hands, Aceh must coexist the national law as well. However, both Aceh’s law and national’s law does not clearly provide the mechanism of handling the pre-election dispute among the regulations. This implies that the provincial election cannot be implemented as long as does not have legal certainty. In the provincial level have suggested making a new bylaw focusing on the local election only, nevertheless, central government have strongly rejected this idea.